Pengujian Validasi Alat Peraga Instalasi Listrik 1 Phase dalam Perkuliahan Fisika Dasar 2 - Martin; Tri Isti Hartini; Imas Ratna Ermawati (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2022)
This study describes specifically the feasibility testing procedure of the 1-phase electrical installation teaching aids that have been developed for the Basic Physics 2 course, Physics Education Study Program, Faculty of Teaching and Education, University of Muhammadiyah Prof. Dr. HAMKA. The instrument used in this study was a response questionnaire for material experts and media experts (lecturers and physics teachers). Feasibility testing is carried out through validation to material experts and media experts. The steps taken in carrying out the validation test are determining the type of instrument, referring to expert theory in compiling a questionnaire grid, compiling a questionnaire grid, and conducting data analysis. The final result of the due diligence test was 87.69% by material experts which consisted of aspects of material relevance, material organization and learning. While the final result for media experts is 86.15% consisting of aspects of media form, media quality and media function. Thus the teaching aids that have been developed have fulfilled the validity procedure with a very valid category.